2016
DOI: 10.1016/j.jcma.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of traditional Chinese medicine for the treatment of influenza A (H1N1): A meta-analysis

Abstract: The results of our study indicated that the mean time to defervescence in the TCM treatment group was less than noted in the control group, and that the duration of viral [Influenza A (H1N1)] shedding in the integrated Chinese and Western medicine subgroups was less than that noted in the control group. However, the available evidence does not consider the fact that the difference in duration of viral shedding and effective rate between the two groups was statistically similar. No obvious adverse events were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Eight [2633] review the effectiveness of pandemic influenza vaccine in preventing influenza and influenza-like illness (ILI); three [3436] examine the impact of antivirals; two [32, 37] review the effectiveness of seasonal influenza vaccines in preventing pandemic influenza infection; two evaluate the impact of personal protective measures (hand-washing, mask use) [38, 39]; one [40] analyzes the impact of school closure; and another [41] reviews the efficacy of traditional Chinese medicine (TCM). One review [42] evaluates the economic viability of a wide range of pharmaceutical and non-pharmaceutical measures, concluding that social distancing, antiviral prophylaxis, school closure, and vaccination are likely to be cost-effective in all settings, while quarantine is never cost-effective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight [2633] review the effectiveness of pandemic influenza vaccine in preventing influenza and influenza-like illness (ILI); three [3436] examine the impact of antivirals; two [32, 37] review the effectiveness of seasonal influenza vaccines in preventing pandemic influenza infection; two evaluate the impact of personal protective measures (hand-washing, mask use) [38, 39]; one [40] analyzes the impact of school closure; and another [41] reviews the efficacy of traditional Chinese medicine (TCM). One review [42] evaluates the economic viability of a wide range of pharmaceutical and non-pharmaceutical measures, concluding that social distancing, antiviral prophylaxis, school closure, and vaccination are likely to be cost-effective in all settings, while quarantine is never cost-effective.…”
Section: Resultsmentioning
confidence: 99%
“…[41] examined the effect of Chinese medicines, herbs, extracts, or other ingredients in reducing the duration of viral shedding in individuals infected with pandemic H1N1, both alone and in combination with oseltamivir treatment. In a meta-analysis of 12 studies (n = 1,469), using oseltamivir treatment as a control, the mean duration of viral shedding did not differ significantly between the TCM and oseltamivir treatment groups (mean difference 0.07 days; 95% CI -0.07–0.21).…”
Section: Resultsmentioning
confidence: 99%
“…Traditional Chinese medicinal herbs may be a potential alternative medicine source for treatment31. Recently, clinical trials have shown that TCMs, including Lonicera japonica Thunb, could be alternative treatments for influenza32. CHA exists in high quantities in Lonicera japonica Thunb33, which is an inexpensive and widely distributed resource.…”
Section: Discussionmentioning
confidence: 99%
“…For example, China's Ministry of Health recommended using extracts from some natural herbs that have beneficial immunomodulatory effects (26). More and more scientific data suggest that probiotic bacteria can be effectively used to decrease the risk or duration of influenza symptoms.…”
Section: Probiotic Bacteria Inhibit Influenza Virusmentioning
confidence: 99%